IMPLEMENTASI PSAK 22 TENTANG KOMBINASI BISNIS DAN DAMPAKNYA TERHADAP PENYAJIAN LAPORAN KEUANGAN BANK SYARIAH INDONESIA (BSI) HASIL MERGER TAHUN 2021 - Fatima Nur Janah; Haniifah Khoirunnisaa; Anna Nailul Farchani; Devina Triarshinta; Endang Kartini Panggiarti (CV. Denasya Smart Publisher, 2026)
A merger is a corporate strategy that aims to strengthen capital structure, expand business scope, and improve operational efficiency. On February 1, 2021, three state-owned Islamic banks, namely Bank Syariah Mandiri, BNI Syariah, and BRI Syariah, officially merged to form Bank Syariah Indonesia (BSI), making it the largest merger in the history of Islamic banking in Indonesia. This study aims to analyze the application of PSAK 22 in the merger process, particularly regarding the assessment of the fair value of assets and liabilities, the recognition of goodwill, and the quality of disclosure in the consolidated financial statements. This study utilizes a qualitative descriptive approach by analyzing BSI's 2021–2023 financial audit reports, OJK publications, and IAI regulations. The findings indicate that BSI has met the formal compliance standards of PSAK 22 through the implementation of the Purchase Price Allocation (PPA) and the evaluation of goodwill impairment. However, transparency regarding the valuation methodology, cash flow assumptions, discount rates, and valuation sensitivity is still lacking, giving rise to the risk of information asymmetry and the possibility of goodwill overvaluation. Therefore, increased transparency in disclosure is necessary to ensure that the quality of BSI's reporting is comparable to global best practices and to strengthen stakeholder confidence after the merger.